Implementasi Akad Wadi’ah Pada Perbankan Syariah - Johari, Elman; Septian Kurniawan, Septian (El-kahfi | Jurnal Ekonomi Islam, 2023)
Nowadays, the problem of saving funds is in banking institutions, usually through a system of savings, current accounts and deposits. Deposits (Al-Wadiah) in Wadi‟ah are taken from the word wada‟a, which means to leave because the mandate is left to someone else who receives the deposit. Muhammad bin Ibrahim al-Tuwaijir defines wadi‟ah as property that is handed over to someone else who looks after it without compensation, such as entrusting someone else's hours, cars or money. Wadi‟ah is a contract between two people in which the first party delegates the task and power to the second party to maintain his property. In the implementation of the wadiah contract, certain pillars and conditions must be met. Al-Jaziri expressed the opinion of the imam of the madhhab as follows. According to Hanafiah, alwadiah has one pillar, namely consent and qabul. According to Hanafiah, in sighah, the consent is considered valid if it is done in a clear language (sharia). This also applies to Kabul, the requirements for consignors and trustees and Mukala goods. It is not valid if the person entrusted to take the deposit is a madman or shabiy. To obtain orientit profit, some scholars allow it, and some do not allow it. If the item is intentionally damaged or lost, the stored item must be replaced, in the event of an accident there must be an agreement from the owner.